Cultivar Grain Yield in Durum Wheat-Grain Legume Intercrops Could Be Estimated From Sole Crop Yields and Interspecific Interaction Index - Kammoun, Bochra; Journet, Etienne-Pascal; Justes, Eric; Bedoussac, Laurent (Frontiers in Plant Science, 2021)
Ensuring food security for a world population projected to reach over nine billion by 2050 while mitigating environmental impacts and climate change represent the major agricultural challenges. Diversification of cropping systems using notably cereal–legume mixtures is one key pathway for such agroecological intensification. Indeed, intercropping is recognized as a practice having the potential to increase and stabilize yields in comparison to sole crops while limiting the use of inputs notably when species exploit resources in a complementary way. However, predicting intercropped species grain yield remains a challenge because species respond to competition through complex genotype x cropping mode interactions. Here, we hypothesized that grain yield achieved by a cultivar in low nitrogen input durum wheat–grain legume intercrops could be estimated using a few simple variables. The present work is based on a two-year field experiment carried out in southwestern France using two durum wheat (Triticum turgidum L.), four winter pea (Pisum sativum L.) and four winter faba bean (Vicia faba L.) genotypes with contrasting characteristics, notably in terms of height and precocity, to explore a wide range of durum wheat–grain legume phenotypes combinations in order to generate variability in terms of yield and species proportion. The major result is that yield of durum wheat–grain legume intercrop component in low nitrogen input conditions could be correctly estimated from only three variables: (i) wheat cultivar full density sole crop yield, (ii) legume cultivar half density sole crop yield, and (iii) an indicator of legume cultivar response to interspecific competition. The latter variable, the interspecific interaction index, reveals cultivars competitive abilities and tolerance to competition. However, to propose generic intercrop design and management procedures, further mechanistic understanding is required to better understand the links between tolerance to interspecific competition and cultivar phenotype characteristics. In particular, a special emphasis to the grain legume is needed as their response to interspecific competition appears less predictable than that of durum wheat. Cultivar choice is a key element to optimize functional complementarity and subsequent intercrop advantages. This work proposes a simple tool to assist the design of specific breeding programs for cultivars ideotypes adapted to intercropping.